Analysis of Archival Access Policy and Static Archive Services in Compliance with Public Information Disclosure Principles: A Study of Normative Framework and Best Practice - Mualim, Wildan Maulana Assani; Marta, Fitri Yul Dewi; Meiyenti, Ira (Pusat Riset dan Inovasi Nasional, 2026)
Static archives serve as an important source of public information to support state transparency and accountability. This article analyzes the policy of archive access and static archive services within the framework of Law Number 14 of 2008 concerning Public Information Disclosure through a review of normative literature and a review of best practices. This research uses content analysis methods applied to regulations, guideline documents from the National Archives of the Republic of Indonesia (ANRI), and related academic literature. The findings show that the static archive access policy in Indonesia has established the principle of universal openness with strict access restrictions based on legal provisions. However, there is a significant gap between the normative legal framework and practical implementation in the field, especially related to archive management, the availability of search tools, and coordination between archival units and public information management officials. In addition, the low quality of digital infrastructure and the uneven technical competence of archival officers have slowed down the information service process. The recommendations submitted include strengthening the capacity of human resources, integrating the archival information system with the public information disclosure portal, and harmonizing information classification policies so that static archive services can run more effectively and responsive to public needs.